2009
DOI: 10.3171/2008.3.17432
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and brain damage after microsurgical clip occlusion or endovascular coil embolization for ruptured anterior communicating artery aneurysms: neuropsychological assessment

Abstract: Object For anterior communicating artery (ACoA) aneurysms, endovascular coil embolization constitutes a safe alternative therapeutic procedure to microsurgical clip occlusion. The authors' aim in this study was to evaluate the quality of life (QOL), cognitive function, and brain structure damage after the treatment of ruptured ACoA aneurysms in a group of patients who underwent microsurgical clipping (36 patients) compared with a reference group who underwent endovascular coiling (14 patients). Methods At 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 53 publications
2
54
1
3
Order By: Relevance
“…Although it may be possible to perform the same analysis by using conventional 2D 2-or 3-mm coronal imaging with/without axial images, we presume that 3D MR imaging by using MPR could more easily identify small structures in the basal forebrain. Indeed, a recent neuropsychological study by Proust et al 5 revealed the high prevalence of verbal memory deficits (58.3%) among 36 patients with variably decreased intellectual function after ACoA clipping. Regarding verbal memory deficits, Guglielmi 14 stated, in his letter to the editor, that ACoA syndrome is likely due to occlusion of the subcallosal artery.…”
Section: Diagnostic Value Of 3d Mr Imaging In Patients With Basal Formentioning
confidence: 99%
See 2 more Smart Citations
“…Although it may be possible to perform the same analysis by using conventional 2D 2-or 3-mm coronal imaging with/without axial images, we presume that 3D MR imaging by using MPR could more easily identify small structures in the basal forebrain. Indeed, a recent neuropsychological study by Proust et al 5 revealed the high prevalence of verbal memory deficits (58.3%) among 36 patients with variably decreased intellectual function after ACoA clipping. Regarding verbal memory deficits, Guglielmi 14 stated, in his letter to the editor, that ACoA syndrome is likely due to occlusion of the subcallosal artery.…”
Section: Diagnostic Value Of 3d Mr Imaging In Patients With Basal Formentioning
confidence: 99%
“…[1][2][3][4][5][6] On the basis of descriptions from the 1970s of the perforating branches from the ACoA, 7 much indirect evidence indicates that the amnesia is caused by damage or occlusion of the perforators of the ACoA, and this is known as ACoA syndrome. 2,8,9 Gade 10 linked vascular damage of the perforators from the ACoA during surgery with postoperative amnesia not directly, but clearly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,[6][7][8][9][10] In the past 2 decades, the inherently less invasive endovascular approach has emerged as a feasible and acceptable treatment option for AcomA aneurysms. [11][12][13][14] Continual advancements in endovascular technique and adjuvant devices have led to an enlarging proportion of patients with AcomA aneurysms who are successfully treated with coil embolization. 10,11,15,16 A limited number of case series have detailed the clinical outcomes, angiographic results, and procedure-related complications specific for endovascular treatment in this location.…”
mentioning
confidence: 99%
“…Approximately 30-35% of the intracranial aneurysms were located in ACoA (Osborn, 1994). Needless to emphasize, endovascular embolization occupies a very important position in the treatment of aneurysms (Proust et al, 2009). The therapeutic microcatheter must be negotiated through the ICA and across the A1 portion of the anterior cerebral artery to reach the disease site in the ACoA.…”
Section: Discussionmentioning
confidence: 99%